Minimally invasive treatment of pathological fractures of the humeral shaft - Ofluoglu, Onder (Springer-Verlag, 2008)
Most patients with pathological fractures due to cancer metastasis have a limited life expectancy. Orthopaedic procedures, therefore, should be minimally invasive in order to avoid additional surgical morbidity. The purpose of this study was to analyse the results of minimally invasive approaches, including locked intramedullary nailing, followed by early postoperative radiation for pathological humeral shaft fractures. Twenty-four pathological fractures of the humerus diaphysis in 23 patients were treated with the prospective protocol, including antegrade unreamed intramedullary nailing and postoperative radiotherapy (20 Gy and five fractions). The patients and results of the surgery were evaluated by the Musculoskeletal Tumor Society upper extremity scoring system. All patients had a stable extremity, and the average function of 20 patients was 64% of the normal upper extremity function. Only one patient required revision surgery. The minimally invasive treatment of patients with pathological fractures of the humeral shaft with closed unreamed intramedullary nailing combined with adjuvant radiotherapy is an effective and safe procedure, even in seriously ill patients.